Armee et politique au Niger. - Idrissa, Kimba (CODESRIA, 2008)
Niger's political history has lacked a synthesis on the army's involvement in politics since independence. The country is a fertile ground for such analysis. Between 1964 and 1999, the country witnessed three successful military coups during the democratisation process (April 1974, January 1996, and April 1999) and at least four military coup attempts (1964, 1975, 1976, 1983). In its forty years of independence, Niger has been under military rule for twenty-one years. It has also experienced seven different institutional regimes while four out of the six presidents who headed the country were.